Russian Federation : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper for the Russian Federation reviews trends in private capital flows to Russia by decomposing the flows into its subcomponents. Russia became a net lender to the international banking system, as a complement to the prolonged period of large current account surpluses. The nonbank corporate sector in Russia began to have better access to both bank and nonbank sources of external finance, with improving investor perceptions and a favorable external environment. The relatively lackluster performance of equity issuances and foreign direct investment has been an outcome of both global and local factors.